369 An investigation into the influence of the seaweed extract laminarin on post-weaning pig performance and the intestinal microbiome. (5th December 2019) - Vigors, Stafford; O' Doherty, John; McDonnell, Mary; Rattigan, Ruth; Sweeney, Torres
Abstract: Marine macroalgal derivatives such as laminarin have been considered as potential bioactive compounds in swine nutrition to improve post-weaning pig performance. However, a comprehensive understanding of the impact of these extracts on the intestinal microbiome and its subsequent influence on performance is not well characterized. Therefore, the objective of this study was to evaluate the effects of supplementing the diet of newly weaned pigs with laminarin, on animal performance and the intestinal microbiota using 16S rRNA gene sequencing. At 28 days of age, newly weaned pigs (n = 54) were assigned to one of two dietary groups: 1) basal diet and 2) basal diet + 300 ppm laminarin for a 14-day period. On day 15, nine pigs per treatment (one from each pen) were humanely euthanized and high-throughput sequencing of the V3-V4 hypervariable region of the bacterial 16S rRNA gene was performed on the Illumina MiSeq. Pigs fed the laminarin-supplemented diet had increased average daily feed intake, growth rate and body weight compared to pigs fed the control diet (P < 0.05). Pigs fed the laminarin supplemented diet had reduced abundances of Enterobacteriaceae (P < 0.05) compared to pigs fed the control diet. Enterobacteriaceae and Helicobacteraceae had negative relationships with average daily feed intake (ADFI), average daily gain (ADG) and butyric acid concentrations. In contrast, the beneficial Prevotellaceae were positively correlated with ADFI, ADG, total VFA, acetic, propionic, butyric and negatively correlated with isovaleric acid. Hence, supplementation with laminarin may accelerate the adoption of pigs to a post-weaning diet by promoting the proliferation of bacterial species that favourably enhance nutrient digestion and reduce the load of pathogenic bacteria impacting pig performance.